Aptasensing luteinizing hormone to determine gynecological endocrine complications on graphene oxide layered sensor. (1st August 2021) - Sun, Huanhuan; Bao, Xiucui; Yao, Xiaoling; Gopinath, Subash C. B.; Min, Yifei
Abstract: Luteinizing hormone (LH)/lutropin is an interstitial cell‐stimulating hormone playing a predominant role in the reproductive system, and highly correlated with the infertility treatment in both men and women. This research was concentrated to quantify LH level by using interdigitated electrode sensor. To improve the electric current flow, sensing electrode was modified with graphene oxide (GO) and the aptamer probe was attached on GO through biotin‐streptavidin linker. Current responses were measured with aptamer–LH interaction at the target concentrations between 7.5 nM and 1 μM and the detection limit of LH was calculated as 60 nM with the determination coefficient ( R 2 ) value, 0.9229 [ y = 1.296 x − 2.8435] on a linear range from 30 nM to 1 μM. Further, biofouling effect on sensing electrode surface was analyzed with complementary aptamer sequence, control proteins (albumin and globulin). The above GO‐aptamer‐modified interdigitated electrode sensor helps to quantify LH level and diagnose gynecological endocrinology‐related complications. Abstract : Graphical Abstract: